2017
DOI: 10.3390/ijms18091930
|View full text |Cite
|
Sign up to set email alerts
|

MDG-1, a Potential Regulator of PPARα and PPARγ, Ameliorates Dyslipidemia in Mice

Abstract: Hyperlipidemia is a serious epidemic disease caused by lipid metabolism disorder, which is harmful to human health. MDG-1, a β-d-fructan polysaccharide extracted from Ophiopogon japonicus, has been shown to improve abnormal blood lipid levels and alleviate diabetes. However, the underlying mechanism on hyperlipidemia is largely unknown. In this study, male C57BL/6 mice were randomly separated into three groups, respectively: low-fat diet (Con), high-fat diet (HFD), and high-fat diet plus 5‰ MDG-1 (HFD + MDG-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…For example, Chang et al [ 7 ] discovered that Ganoderma lucidum reduced body weight, fat accumulation, inflammation, endotoxemia and insulin resistance in obese mice and prevented obesity-related metabolic disorders in obese individuals. Additionally, it was also reported that MDG-1, a β-D-fructan polysaccharide extracted from Ophiopogon japonicus , could prevent the development of obesity and ameliorate dyslipidemia in high-fat diet (HFD)-induced obese mice [ 9 , 10 ]. Interestingly, a compound polysaccharide, which is a mixture of lentinan and Flos Lonicera polysaccharides (LF), improved obesity and its related complications in our research studies (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chang et al [ 7 ] discovered that Ganoderma lucidum reduced body weight, fat accumulation, inflammation, endotoxemia and insulin resistance in obese mice and prevented obesity-related metabolic disorders in obese individuals. Additionally, it was also reported that MDG-1, a β-D-fructan polysaccharide extracted from Ophiopogon japonicus , could prevent the development of obesity and ameliorate dyslipidemia in high-fat diet (HFD)-induced obese mice [ 9 , 10 ]. Interestingly, a compound polysaccharide, which is a mixture of lentinan and Flos Lonicera polysaccharides (LF), improved obesity and its related complications in our research studies (unpublished data).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, PPAR-γ serves a vital role in adipocyte differentiation, glucolipid metabolism and insulin resistance (24). PPAR-γ is a class of ligand-activated nuclear transcription factor that can regulate the expression of multiple key genes during glucose and lipid metabolism (25). Notably, leptin is involved in regulating glucose and lipid metabolism in the liver (25).…”
Section: Discussionmentioning
confidence: 99%
“…PPAR-γ is a class of ligand-activated nuclear transcription factor that can regulate the expression of multiple key genes during glucose and lipid metabolism (25). Notably, leptin is involved in regulating glucose and lipid metabolism in the liver (25). Consequently, leptin may enhance the synthesis of triglycerides and reduce the production of hepatic glycogen (26).…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of LD-associated proteins such as members of the PLIN family, CIDEC, CIDEA, HILPDA, FITM1, FITM2, and G0S2 by PPAR-γ has been considered as a mechanistic link between lipid uptake and regulation of lipid storage capacity (Montserrat & Kersten, 2017). Mice with dyslipidemia have high PPAR-γ level, whereas PPAR-γ inhibition can prevent HFD-induced hyperlipidemia and obesity Wang, Shi, Joyce, Wang, & Feng, 2017). SIRT1, a protein deacetylase, represses PPAR-γ and inhibits fatty acid biosynthesis (Picard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%